2007
DOI: 10.1016/j.jasms.2007.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Response normalized liquid chromatography nanospray ionization mass spectrometry

Abstract: The widely different LC-MS response observed for many structurally different compounds limits the use of LC-MS in full scan detection mode for quantitative determination of drugs and metabolites without using reference standard. The recently introduced nanospray ionization (NSI) technique shows comparable MS response for some compounds under non-LC-MS conditions. However, in the presence of numerous endogenous compounds commonly associated with biological samples such as urine, plasma, and bile, LC-MS is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…These observations indicate that the signal of a metabolite can be higher or lower than that of the substrate and that none of the different metabolic transformations give a consistently better agreement in the slopes. This result does not appear to be the case for carboxylic acid metabolites (Hop et al, 2005;Valaskovic et al, 2006;Ramanathan et al, 2007) or for the loss of an amine by N-dealkylation (Benetton et al, 2003), both of which consistently show a lower signal for the metabolite. Indeed, the fact that all the compounds tested have multiple nitrogen atoms and no other ioniz- b Slope (average) of the standard curve for metabolite versus internal standard divided by slope (average) of the standard curve for substrate versus internal standard using nanospray ionization.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These observations indicate that the signal of a metabolite can be higher or lower than that of the substrate and that none of the different metabolic transformations give a consistently better agreement in the slopes. This result does not appear to be the case for carboxylic acid metabolites (Hop et al, 2005;Valaskovic et al, 2006;Ramanathan et al, 2007) or for the loss of an amine by N-dealkylation (Benetton et al, 2003), both of which consistently show a lower signal for the metabolite. Indeed, the fact that all the compounds tested have multiple nitrogen atoms and no other ioniz- b Slope (average) of the standard curve for metabolite versus internal standard divided by slope (average) of the standard curve for substrate versus internal standard using nanospray ionization.…”
Section: Discussionmentioning
confidence: 81%
“…In this regard, other methodologies show promise. For example, a number of investigators have used nanospray LC-MS to decrease the differences between the signal from parent drug and metabolites (Benetton et al, 2003;Hop et al, 2005;Valaskovic et al, 2006;Ramanathan et al, 2007). Furthermore, a number of other methods to estimate exposure to a metabolite using corrected responses in LC-MS/MS (Vishwanathan et al, 2009;Gao et al, 2010;Ma et al, 2010;Tong et al, 2010;Mutlib et al, 2011;Walker et al, 2011) or NMR based methods (Vishwanathan et al, 2009;Mutlib et al, 2011;Walker et al, 2011) have been developed.…”
Section: Dahal Et Almentioning
confidence: 99%
“…(Hop et al, 2005). Differences in ionization efficiency of compounds with different physicochemical characteristics are in general reduced by the application of chip-based NSI (Hop et al, 2005;Hop, 2006;Valaskovic et al, 2006;Wickremsinhe et al, 2006;Ramanathan et al, 2007). Recently, the accuracy of nano-electrospray ionization MS response of drug compounds and their respective metabolites from biological matrices compared with accurate radiometric quantification was evaluated, and it has been demonstrated that nanoelectrospray mass spectrometry can be used for semiquantitation of metabolites (Schadt et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Samples obtained from the freeze-dried, 30-m whole-body sections were analyzed using a linear ion trap LTQ/ Orbitrap hybrid mass spectrometer (Thermo Scientific) (Hu et al, 2005) equipped with a TriVersa NanoMate nanospray ion source (Schultz et al, 2000;Ramanathan et al, 2007). For sample extraction from the tissue sections, 1 to 2 l of solvent (ACN/water 50:50 with 0.1% FA) were used.…”
Section: Distribution Of Figopitant and Its Metabolites In Rat Tissuementioning
confidence: 99%
See 1 more Smart Citation